Academic Leadership of Private School Administrators under the Jurisdiction of Rueso District Private Education Office, Narathiwat Province - Latae, Sitipatimoh; Kohtbantau , Sunthon (Journal for Developing the Social and Community, 2022)
The research purposes were: to study the academic leadership of private school administrators under the jurisdiction of Rueso District Private Education Office, Narathiwat Province; and to compare the academic leadership of private school administrators under the jurisdiction of Rueso District Private Education Office, Narathiwat Province, classified by education qualification and school size. The target population was the teachers of private schools under the jurisdiction of Rueso District Private Education Office, Narathiwat Province; the sample group was the 86 teachers. The research instrument was the 5-level estimate rating scale questionnaire with Index of Item Objective Congruence (IOC) between 0.60-1.00, and reliability .98. The data analysis statistics were the percentage, mean, standard deviation, and t-test. The research findings were: The academic leadership of private school administrators under the jurisdiction of Rueso District Private Education Office, Narathiwat Province found the overall was at high level. When each aspect consideration found all aspects were at high level; the descending mean were the curriculum aspect, the professional development aspect, the supervision aspect, the assessment and monitoring of student progress aspect, and the promoting the teaching atmosphere aspect, respectively. The academic leadership comparison of private school administrators under the jurisdiction of Rueso District Private Education Office, Narathiwat Province, classified by education qualification and school size found: (1) the teachers with different of education qualification had the opinion toward the academic leadership comparison of private school administrators under the jurisdiction of Rueso District Private Education Office, Narathiwat Province found the overall and each aspect did not different; and (2) the teachers with different of school size had the opinion toward the academic leadership comparison of private school administrators under the jurisdiction of Rueso District Private Education Office, Narathiwat Province found the overall was different at statistics significance level .05. When each aspect consideration found the curriculum aspect, the supervision aspect, the promoting the teaching atmosphere aspect and the assessment and monitoring of student progress aspect were different at statistics significance level .05; excepted the professional development aspect did not different.